An endophytic fungus isolated from finger millet (Eleusine coracana) produces anti-fungal natural products - Mousa, Walaa K.; Schwan, Adrian; Davidson, Jeffrey; Strange, Philip; Liu, Huaizhi; Zhou, Ting; Auzanneau, France-Isabelle; Raizada, Manish N. (Frontiers in Microbiology, 2015)
Finger millet is an ancient African cereal crop, domesticated 7000 years ago in Ethiopia, reaching India at 3000 BC. Finger millet is reported to be resistant to various fungal pathogens including Fusarium sp. We hypothesized that finger millet may host beneficial endophytes (plant-colonizing microbes) that contribute to the antifungal activity. Here we report the first isolation of endophyte(s) from finger millet. Five distinct fungal species were isolated from roots and predicted taxonomically based on 18S rDNA sequencing. Extracts from three putative endophytes inhibited growth of F. graminearum and three other pathogenic Fusarium species. The most potent anti-Fusarium strain (WF4, predicted to be a Phoma sp.) was confirmed to behave as an endophyte using pathogenicity and confocal microscopy experiments. Bioassay-guided fractionation of the WF4 extract identified four anti-fungal compounds, viridicatol, tenuazonic acid, alternariol and alternariol monomethyl ether. All the purified compounds caused dramatic breakage of F. graminearum hyphae in vitro. These compounds have not previously been reported to have anti-Fusarium activity. None of the compounds, except for tenuazonic acid, have previously been reported to be produced by Phoma. We conclude that the ancient, disease-tolerant crop, finger millet, is a novel source of endophytic anti-fungal natural products. This paper suggests the value of the crops grown by subsistence farmers as sources of endophytes and their natural products. Application of these natural chemicals to solve real world problems will require further validation.